2018
DOI: 10.1002/uog.19042
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of targeted next‐generation sequencing in fetuses with congenital heart defect

Abstract: Targeted NGS in fetuses with isolated and non-isolated CHD achieved a high diagnostic yield in our cohort, with an acceptable turnaround time for the prenatal setting. Our results have important implications for clinical management and genetic counseling. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 30 publications
1
52
0
Order By: Relevance
“…Single‐gene disorders also contribute to CHD in both isolated and syndromic cases. For isolated CHDs an ever‐expanding list of genes is being identified that are directly or indirectly involved in cardiac morphogenesis . Occasionally, genes involved in syndromic CHD can also produce isolated malformations .…”
Section: Other Genetic Syndromes Associated With Cardiac Anomaliesmentioning
confidence: 99%
See 3 more Smart Citations
“…Single‐gene disorders also contribute to CHD in both isolated and syndromic cases. For isolated CHDs an ever‐expanding list of genes is being identified that are directly or indirectly involved in cardiac morphogenesis . Occasionally, genes involved in syndromic CHD can also produce isolated malformations .…”
Section: Other Genetic Syndromes Associated With Cardiac Anomaliesmentioning
confidence: 99%
“…Recently, Hu et al customized a gene panel utilizing NGS to target 77 CHD‐related genes . Evaluation of 44 amniotic fluids from fetuses with sporadic CHD without chromosomal abnormalities identified 13.6% (n = 6/44) pathogenic variants (CHD7, CITED2, ZFPM2, MYH6, KMT2D, JAG).…”
Section: Other Genetic Syndromes Associated With Cardiac Anomaliesmentioning
confidence: 99%
See 2 more Smart Citations
“…The H3K4 methyltransferase KMT2D (MIM 602113)also known as ALR, MLL4, or sometimes MLL2-has been shown to be mutated in patients with congenital heart disease. 1,[5][6][7][8] KMT2D is a large protein with over 5500 amino acids and harbors a C-terminal SET domain, required for H3K4 methyltransferase activity. KMT2D has been shown to catalyze H3K4 mono-, di-or tri-methylation.…”
Section: Introductionmentioning
confidence: 99%